The Distribution of Pre- and Postsynaptic Inhibition at Crustacean Neuromuscular Junctions - Kennedy, Donald (The Rockefeller University Press, 1966)
The relative contribution of pre- and postsynaptic mechanisms to peripheral inhibition has been analyzed in the abdominal slow flexor muscles of crayfish and lobsters. The conductance of the muscle fiber membrane may be increased to five or more times its resting value by repetitive stimulation of the peripheral inhibitory axon, and this effect accounts for all of the attenuation exerted by the inhibitor against excitatory junctional potentials. No "critical interval" has been found at which an inhibitory nerve impulse produces anomalously large reduction of a following depolarizing junctional potential; electrotonic depolarizations and junctional potentials are identically affected under all phase conditions. The presynaptic inhibitory mechanism is, therefore, absent in this system. In the dactyl opener muscle, on the contrary, most of the attenuation of excitatory junctional potentials is achieved presynaptically, though equally large postjunctional conductance changes are also seen (Dudel and Kuffler, 1961). The difference is correlated with a difference in the reflex operation of the two muscles. Reflex inhibition in the abdominal slow flexors is primarily central, whereas in the dactyl opener, inhibition is brought about by an increase in inhibitory nerve discharge frequency without central suppression of the single excitatory axon. The function of peripheral inhibition in the abdominal flexors is presumably to terminate residual depolarization by reducing the long time-constant of the muscle fibers.